Citra Perempuan dalam Novel Perempuan Berkalung Sorban Karya Abidah El-Khaliqy: Indonesia - Indriati Lewa; Muhammad Syafri Badaruddin; Ikki Pramatasari Kadir Ikki (Hasanuddin University, 2021)
Ikki Pramatasari Kadir. Image Of Women in the Novel Perempuan Berkalung Turban by Abidah El Khalieky: An Overview of Feminist Literary Criticism. This study aims to reveal the forms of gender injustice experienced by female characters that occur in Abidah El Khalieqy's novel Perempuan Berkalung Sorban. The data collection method used in this research is literature study method. This research uses tools, namely, books, journals, and articles from the internet that have a relationship with primary data. The results showed that there was a picture of gender injustice in the form of subordination experienced by female figures. Keywords: Subordination, novel, literary criticism.